Pidiendo Caridad en la Ciudad. Mujeres y niños indígenas en las calles del Ecuador de Kate Swanson - Erika Bedón (Íconos)
Resumen de Pidiendo Caridad en la Ciudad. Mujeres y niños indígenas en las calles del Ecuador